2021
DOI: 10.1038/s41598-021-97149-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel variants in Krueppel like factor 1 that cause persistence of fetal hemoglobin in In(Lu) individuals

Abstract: Beta-hemoglobinopathies become prominent after birth due to a switch from γ-globin to the mutated β-globin. Haploinsufficiency for the erythroid specific indispensable transcription factor Krueppel-like factor 1 (KLF1) is associated with high persistence of fetal hemoglobin (HPFH). The In(Lu) phenotype, characterized by low to undetectable Lutheran blood group expression is caused by mutations within KLF1 gene. Here we screened a blood donor cohort of 55 Lutheran weak or negative donors for KLF1 variants and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Interestingly, the KLF1 variant alleles found in two donors are characterised by combinations of the above mentioned polymorphisms in cis , as c.[304T>C, 1001C>G] and c.[304T>C, 519_525dupCGGCGCC]. Although the effects of missense variant c.304T>C have been reported to cause the In(Lu) phenotype in the early publication, this variant has been shown by three groups to have no impact on Lu a and Lu b expression [ 26 , 31 , 32 ]. Helias et al [ 26 ] showed c.304T>C is relatively frequent in general population and thus could not be responsible for the rare In(Lu) phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the KLF1 variant alleles found in two donors are characterised by combinations of the above mentioned polymorphisms in cis , as c.[304T>C, 1001C>G] and c.[304T>C, 519_525dupCGGCGCC]. Although the effects of missense variant c.304T>C have been reported to cause the In(Lu) phenotype in the early publication, this variant has been shown by three groups to have no impact on Lu a and Lu b expression [ 26 , 31 , 32 ]. Helias et al [ 26 ] showed c.304T>C is relatively frequent in general population and thus could not be responsible for the rare In(Lu) phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The LU (now BCAM) gene is located on chromosome 19 at 19q13. 32 and is organised into 15 exons distributed over approximately 12.5 kb. The Lu a and Lu b antigens have codominant allelic relationships and represent a single nucleotide variant (SNV), rs28399653, c.230A>G (p. His77Arg) in exon 3 of the BCAM gene [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has emerged that KLF1 contributes to control adult and fetal globin gene expression. Accordingly, several reports have revealed that heterozygosity for loss-of-function mutations in KLF1 can ameliorate the severity of hemoglobinopathies by leading to persistent fetal globin gene expression in adult life (HPFH) [ 13 , 24 , 52 , 53 , 54 ]. Therefore, besides providing crucial information about the molecular processes that regulate the transcriptional regulation of the human fetal globin genes, these conditions have gained considerable clinical interest, given the potential therapeutic role of increased HbF levels in hemoglobinopathies.…”
Section: Discussionmentioning
confidence: 99%
“…A perplexing observation in the field is the extensive variation in HbF levels seen in individuals containing the same monoallelic KLF1 mutation, even within the same family pedigree 16 , 29 , 95 . This was also seen in our own studies (comparison of the dual gRNA data between Figs.…”
Section: Discussionmentioning
confidence: 99%
“…3 and 4 ). This is thought to be due to variable penetrance and microvariation of KLF1 expression as contributed by additional mutations on the remaining WT allele 76 , 95 . Our data suggest that the overall architecture of the KLF1 genomic region is buffered against localized changes having a substantive effect on its expression.…”
Section: Discussionmentioning
confidence: 99%